2013
DOI: 10.1186/1472-6920-13-161
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional education in primary care for the elderly: a pilot study

Abstract: BackgroundThe Dutch health care system faces huge challenges with regard to the demand on elderly care and the competencies of nurses and physicians required to meet this demand.At present, the main focus of health care in the Netherlands lies on illness and treatment. However, (frail) elderly need care and support that takes their daily functioning and well-being into consideration as well. Therefore, health care professionals, especially those professionals working in primary care such as GPs and practice nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…Thus, a shift to include more preventive care of the elderly occurred after the IPE intervention using a team approach to elder care. [15] Citing teamwork skills as a foundational component of inter-professional collaboration, Shrader, Kern, Zoller and Blue [16] tested whether interprofessional teamwork skills would predict clinical outcomes in a simulated health care situation. Students of medicine, nursing, pharmacy and physician assistant schools were combined in simulation teams.…”
Section: Current Literaturementioning
confidence: 99%
“…Thus, a shift to include more preventive care of the elderly occurred after the IPE intervention using a team approach to elder care. [15] Citing teamwork skills as a foundational component of inter-professional collaboration, Shrader, Kern, Zoller and Blue [16] tested whether interprofessional teamwork skills would predict clinical outcomes in a simulated health care situation. Students of medicine, nursing, pharmacy and physician assistant schools were combined in simulation teams.…”
Section: Current Literaturementioning
confidence: 99%
“…The 2006 census in Iran also showed that the population of people aged sixty or more was around 7.27% of the total population. This rate is estimated to reach 25% -30% by 2030 (3). The increasing number of elderly people and the adverse physical, mental, and socioeconomic effects of aging highlight the importance of paying special attention to the physical, mental, and socioeconomic needs of elderly people.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, interprofessional education becomes necessary to carry out this change in professional behavior, as it can play a fundamental role in improving the skills of professionals to provide care for the elderly in an effective, integrated and coordinated way. 23 In Brazil, this situation is not different, because despite the many investments and policies related to public health in Brazil, for example, the creation of SUS and PNSPI, providing for priority health promotion, the practice of care is also very focused on the biomedical model, the curative dimension, and welfare, critical on the national scene.…”
Section: Strategies That Can Be Used By Nurses and Other Health Profementioning
confidence: 99%
“…However, older people need care and support for the promotion of active aging, not just to treat diseases. 23 Thus, health professionals have been challenged to a paradigm change in emphasis from treating diseases to health promotion (active aging). In this context, interprofessional education becomes necessary to carry out this change in professional behavior, as it can play a fundamental role in improving the skills of professionals to provide care for the elderly in an effective, integrated and coordinated way.…”
Section: Strategies That Can Be Used By Nurses and Other Health Profementioning
confidence: 99%